On the indeterminacy of determinacy and indeterminacy - Andreas Beyer; Roger E. A. Farmer (European Central Bank (ECB), 2003)
A number of authors have attempted to test whether the U.S. economy is in a determinate or an indeterminate equilibrium. We argue that to answer this question, one must impose a priori restrictions on lag length that cannot be tested. We provide examples of two economic models. Model 1 displays an indeterminate equilibrium, driven by sunspots. Model 2 displays a determinate equilibrium driven by fundamentals. Given assumptions about the shock distribution of model 2, it is possible to find a distribution of sunspot shocks that drive model 1 such that the two models are observationally equivalent.
Keywords: C39; C62; D51; 330; Identification; indeterminacy